Can AI Make Fair Triage Decisions? Navigating Algorithmic Bias in Digital Health - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2022)
The integration of Artificial Intelligence AI into healthcare is rapidly transforming clinical workflows, with one of the most critical applications being me...
Keywords: Digital Health; Artificial Intelligence; Healthcare Innovation; Patient Care; Medical AI